Prevalence of left ventricular dysfunction in rheumatoid arthritis - A S Renjith (Journal of Family Medicine and Primary Care, 2017)
Background: Rheumatoid arthritis (RA) is a polyarticular disorder with many extra-articular features. Cardiovascular disorders, including heart failure (HF), are the leading causes of mortality in RA patients. We studied the prevalence of left ventricular dysfunction (LVD) in patients with RA. Materials and Methods: In this cross-sectional study, we evaluated 100 consecutive patients with RA (aged> 18 years and duration> 1 year) for the presence of LVD. We excluded patients with known cardiac and systemic disorders that may contribute to LVD. LVD is defined by the presence of either left ventricular systolic dysfunction (LVSD) or left ventricular diastolic dysfunction (LVDD), evaluated by the echocardiography. Descriptive statistics and relevant tests were used to analyze the results. Results: The study participants (n = 100; 80F and 20M) had a mean age of 45 ± 11.8 years, duration of disease 7.4 ± 5.4 years, and disease activity score of 3.5 ± 1.1. A total of 46 patients had symptoms of HF, but only 14% of them had signs of HF. LVD was seen in 59 (LVSD-4, LVDD-50, and both together in 5) patients, and none of the participants had severe grades of LVSD and LVDD. LVD showed no relation to the age of the patients (P = 0.186) and it was more with increasing duration of RA (P < 0.001) and higher disease activity (P = 0.042). Conclusion: LVD is more common in RA patients, which increases the associated morbidity and mortality. Higher threshold is required by the family practitioners to perform a screening echocardiography in long-standing RA patients.